Method for addressing bottleneck problems in district heating networks - Brange, Lisa; Sernhed, Kerstin; Thern, Marcus (International Journal of Sustainable Energy Planning and Management, 2019)
To work with lowering the system temperatures in district heating (DH) grids is an important factor for system efficiency. Lower system temperatures are related to for example heat losses and production unit efficiency. One obstacle to lower supply temperatures are so called bottlenecks in DH networks. Bottlenecks are areas in the DH network that have very low differential pressure, which makes it difficult to supply them with enough heat. There are many possible solutions to bottlenecks, but presently the decision making process most often do not include all possible bottleneck solutions and also often do not include all important factors affecting the outcome. The aim of this study is to propose a structured and general modus operandi, in order to find the best bottleneck solution for a specific situation. In this study we conducted analyses of previous bottleneck studies, workshops and interviews. The results show a decision making process developed to be a tool when choosing a bottleneck solution. Coupled to the decision making process, a summary of advantages and disadvantages for different factors and bottlenecks solutions is presented, as well as a real case where the decision making process is used.